Agent-Based Modeling of COVID-19 Transmission in Philippine Classrooms - Macalinao, Rojhun O.; Malaguit, Jcob C.; Lutero, Destiny S. (Frontiers in Applied Mathematics and Statistics, 2022)
Schools in the Philippines have suspended face-to-face classes due to the SARS-COV-2 virus which causes the COVID-19. Human interaction transmits the virus, with transmission being faster in closed spaces such as classrooms. An agent-based model was formulated to assess the effects of student-to-student and student-teacher interactions under common classroom layouts in the Philippines. Results show that several factors such as maximum number of students, varying number of initially infected individuals, and allowing within-class mobility and class rotations significantly affect the likelihood of infection apart from the seating arrangement itself. To minimize the risk of transmission, it is vital to control these factors by adhering to mitigation efforts such as increased testing and symptom checking, limiting maximum number of students, and redefining breaks and class rotations. This model can be used for other classroom layouts